Effects of Solid-State Fermented Wheat Bran on Growth Performance, Immune Function, Intestinal Morphology and Microflora in Lipopolysaccharide-Challenged Broiler Chickens - Jishan An; Jingjing Shi; Kuanbo Liu; Aike Li; Beibei He; Yu Wang; Tao Duan; Yongwei Wang; Jianhua He (Animals, 2022)
The study evaluated the effects of dry and wet solid-state fermented wheat bran (FWB) on growth performance, immune function, intestinal morphology and microflora in lipopolysaccharide (LPS)-challenged broiler chickens. The experiment was designed as a 2 × 3 factorial arrangement. A total of 252 one-day-old Arbor Acres male broiler chickens were randomly allocated to 1 of 6 treatments: basal diet + sterile saline (negative control, NC), basal diet + LPS (positive control, PC), 7% dry FWB + sterile saline (FWB-I), 7% dry FWB + LPS (FWB-II), 7% wet FWB + sterile saline (FWB-III) and 7% wet FWB + LPS (FWB-IV), with containing 6 replicate cages/treatment and 7 broiler chickens/cage, and the experimental period lasted for 42 days. Broilers were intraperitoneally injected with either 0.5 mg LPS or sterile saline solution per kg body weight at 16, 18 and 20 d of age. Growth performance, serum immunological parameters and indicators related to intestinal health were analyzed on days 21 and 42. Compared with NC, dry and wet FWB significantly increased (p < 0.05) average daily feed intake of days 21 to 42, and increased (p < 0.05) the villus height and villus height to crypt depth ratio of ileum on day 21, decreased (p = 0.101) the jejunum crypt depth and decreased (p < 0.05) the Lactobacillus and Bifidobacterium counts of the cecum digesta on day 42. Compared with NC, FWB-II and FWB-IV significantly increased (p < 0.05) the levels of serum total protein and globulin on day 21; compared with the basal diet groups, dry and wet FWB groups significantly increased (p < 0.05) glucose levels on day 21, and wet FWB significantly decreased (p < 0.05) alanine aminotransferase levels on day 42. Compared with PC and FWB-II, FWB-IV significantly increased (p < 0.05) the level of serum immunoglobulin G on day 21. Compared with PC and FWB-II, FWB-IV significantly decreased (p < 0.05) the levels of serum pro-inflammatory cytokines interleukin (IL)-6, IL-8, IL-1β and acute C reactive protein (CRP) on day 21; compared with FWB-III, FWB-IV significantly decreased (p < 0.05) the levels of IL-6, IL-8, CRP and tumor necrosis factor alpha on day 42, but the levels of IL-4 and IL-10 were significantly increased (p < 0.05) on days 21 and 42. These results indicated that supplementing 7% dry or wet FWB can improve growth performance and serum immune functions of broilers, which effectively alleviate the LPS-challenged damage, and wet FWB had a better effect than dry FWB.